2019
DOI: 10.1145/3373464.3373470
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for streaming data

Abstract: Incremental learning, online learning, and data stream learning are terms commonly associated with learning algorithms that update their models given a continuous influx of data without performing multiple passes over data. Several works have been devoted to this area, either directly or indirectly as characteristics of big data processing, i.e., Velocity and Volume. Given the current industry needs, there are many challenges to be addressed before existing methods can be efficiently applied to real-world prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(44 citation statements)
references
References 92 publications
0
43
0
1
Order By: Relevance
“…The problem is more aggravated in the case of event streams as the data points, i.e., events, are behaviorally connected. Hassani et al (2019), similar to the techniques prevalent in data stream processing such as summarization (Bahri et al, 2021;Gomes et al, 2019), suggested maintaining an abstract intermediate representation of the stream to be used as input for various process discovery techniques. Online conformance checking techniques in general assume unbounded memory.…”
Section: Related Workmentioning
confidence: 99%
“…The problem is more aggravated in the case of event streams as the data points, i.e., events, are behaviorally connected. Hassani et al (2019), similar to the techniques prevalent in data stream processing such as summarization (Bahri et al, 2021;Gomes et al, 2019), suggested maintaining an abstract intermediate representation of the stream to be used as input for various process discovery techniques. Online conformance checking techniques in general assume unbounded memory.…”
Section: Related Workmentioning
confidence: 99%
“…This can be an abrupt event in the data stream, but it also can be a gradual, reoccurring or even virtual process [26]. Gomes et al [27] mention other possible research directions within incremental learning like anomaly detection [28], ensemble learning, recurrent neural networks and reinforcement learning.…”
Section: Related Workmentioning
confidence: 99%
“…Although much work has been done on concept drift [ 5 7 ], the class imbalance problem [ 11 ] (i.e., negative class instances are more extensive than other classes) further increases the difficulty of addressing concept drift [ 12 ]. Class imbalance commonly exists in the real world.…”
Section: Introductionmentioning
confidence: 99%